Multisymptom Oral Presentation in Type II Diabetes Mellitus: A Case of Candidiasis, Xerostomia, and Burning Mouth Syndrome - Arina Shafia (Al Makki Health Informatics Journal, 2025)
Background: Oral candidiasis is a fungal infection of the tongue and oral mucosa caused by Candida species, characterized by overgrowth and superficial tissue invasion. One of the main predisposing factors is an immunocompromised state such as type II diabetes mellitus. Fungal infections in diabetic patients may be associated with additional oral symptoms, including Burning Mouth Syndrome (BMS) and xerostomia. Case Presentation: A 53-year-old male presented with a three-day history of burning sensation localized to the left side of the tongue. The complaint had not been previously treated. The patient reported a reduced sense of taste, limited to salty and spicy sensations, and persistent dry mouth. Medical history revealed a diagnosis of type II diabetes mellitus for six years, with discontinuation of antidiabetic medication over the past three months. Management and Outcome: The treatment plan included chlorinated dioxide mouthwash (used three times daily), xylitol (taken three times daily), nystatin oral suspension (applied four times daily), a single dose of fluconazole 150 mg, and Becomzet (taken once daily). The patient was instructed to maintain strict adherence to the medication regimen, practice good oral hygiene, and attend regular follow-ups. Improvement in symptoms was observed after consistent use of the prescribed therapy. Conclusion: Effective management of oral candidiasis in patients with poorly controlled type II diabetes mellitus, particularly when accompanied by Burning Mouth Syndrome and xerostomia, requires a comprehensive treatment approach. Success is largely dependent on accurate drug selection and patient compliance with therapy and oral hygiene practices. This case highlights the importance of addressing systemic factors in conjunction with local treatment to ensure resolution of symptoms and prevent recurrence.